An attachment-based framework for disordered personality development: Implications for intersubjective psychodynamic psychotherapy - Brambilla, Paolo; Bressi, Cinzia; Biagianti, Bruno (Frontiers in Psychiatry, 2022)
Infant-caregiver dyads show high heterogeneity in terms of compatibility. Several lines of evidence indicate that the modalities by which areas of good and poor fit were emotionally recognized and managed by caregivers influence the infant's personality development, the integration of their personality traits, the overall sense of authenticity, as well as the modalities of transference that typically manifest during psychodynamic psychotherapy. Within an intersubjective framework, the relationship between patient and psychotherapist will inevitably recreate compatibility issues, although the specific areas of incompatibility will likely differ from the scenarios present in the caregiver relationship. In other words, emotional friction may originate from personality traits that were not problematic in the first place. The author hypothesizes that disclosure of the challenges associated with the management of areas of incompatibility will not only promote emotional honesty within the dyad, but also offer an excellent opportunity for introjection. Such disclosures are not at risk of being interpreted as an attempt to build an intersubjective experience, but represent a window into authenticity, which in turn enables patients to develop awareness of their personality and relational traits, along with the challenges and vulnerabilities that occur when such traits interface with otherness.